A comprehensive study of the opposition effect on 15 NEOs. Issue 2 (25th April 2022) - Ieva, S; Arcoverde, P; Rondón, E; Giunta, A; Dotto, E; Lazzaro, D; Mazzotta Epifani, E; Perna, D; Fanasca, C; Rodrigues, T; Monteiro, F; Medeiros, H; et al.
ABSTRACT: We report the results we derived analyzing photometric measurements obtained at different phase angles for 15 Near-Earth Objects (NEOs), observed from Campo Imperatore observatory, and Observatório Astronômico do Sertão de Itaparica (OASI). The performed analysis allows us to taxonomically classify them using several independent techniques, thus constraining their surface composition. The majority of this sample is in agreement with a pristine carbonaceous composition (C-complex/D-type asteroids), while few NEOs are composed of more evolved (e.g. S/M/E-type bodies) material. With this work we made evident that a comprehensive characterization of a NEO can be achieved through the coupling of spectrophotometric data and phase curve assessment. This is crucial in case these objects become target of future rendez-vous, sample-return or mitigation missions.